Key Factors of Non-performing Loans in Baltic and Scandinavian Countries: Lessons Learned in the Last Decade - Kupčinskas, Kazys; Paškevičius, Arvydas (Ekonomika, 2017)
A cross-country panel data regression was performed for non-performing loans (NPL) in Denmark, Estonia, Finland, Latvia, Lithuania and Sweden covering a period of years 1998-2014. The main objective was to determine the major factors that were driving the NPL in the selected countries. Also, we expected to draw the differences in the banking industry between emerging economies in the Baltic countries and Western economies in the Scandinavian region. The selected variables were banking industry-related (net interest margin, ROA, ROE) and macroeconomic variables (GDP growth, RE prices, Unemployment), of which the majority is included as the Financial Soundness Indicators by the IMF. Key findings of the research show that NPL in both regions were mostly dependent on GDP growth and Unemployment, whereas the banking industry variable ROA had a very moderate effect only on a country level. The research is contributing to a better understanding of financial stability in the banking industry during the last decade, and it may have possible implications for the macroprudential policy.
Keywords: non-performing loans; credit risk